DRES-05. MOLECULAR EVOLUTION OF DIFFUSE GLIOMAS AND THE GLIOMA LONGITUDINAL ANALYSIS CONSORTIUM. (5th November 2018) - Verhaak, Roel; Consortium, GLASS; Aldape, Kenneth; Amin, Samirkumar; Ashley, David; Barnholtz-Sloan, Jill; Bates, Amanda; Beroukhim, Rameen; Bock, Christoph; Brat, Daniel; Claus, Elizabeth; Costello, Joseph; et al.
Abstract: A comprehensive characterization of the somatic alterations and molecular subtypes of glioma at diagnosis has been established. However, gliomas undergo significant molecular changes over time, some of these causing malignant progression or associated with therapy. Understanding this molecular evolution may uncover therapeutic vulnerabilities and facilitate development of more effective systemic therapies. The Glioma Longitudinal Analysis (GLASS) Consortium is an international effort to systemically catalogue the longitudinal changes in gliomas through multi-platform characterization. GLASS has developed computational and clinical infrastructure to enable its mission of establishing a well annotated longitudinal molecular dataset of 1500 gliomas including 500 gliomas per each of the IDHwt/IDH-mut-non-codel/IDH-mut-codel subtypes. An initial dataset comprising 150 cases with exome sequencing at multiple timepoints has been constructed, including cases diagnosed as IDHwt (55%), IDH-mut-non-codel (38%) and IDH-mut-codel (6%). Treatment regimens followed the expected combinations of chemo- and radiation therapy while survival was more favorable than reported in literature, suggested a bias in our dataset towards better performing cases. This is possibly explained by the need for two consecutive surgical procedures to be included in the analysis. While more than half of mutations in IDHwt primary tumors were recovered in their matching recurrences, this fraction was less than 30% in the other two subtypes. The disparity in mutations between primary and recurrences may reflect intratumoral heterogeneity in both primary and recurrence, and clonal selection patterns. We observed temozolomide treatment-associated hypermutation in up to 13 of our cohort. A more detailed analysis of mutational and DNA copy number data is underway. A cohort of 75 additional patients with multi-timepoint exome data is being processed and, through several funded projects, multi-platform characterization of 250 gliomas is in progress. In summary, GLASS will provide a rich resource to the glioma community with the potential for paradigm shifting discoveries.